MEDIA EDUKASI E-POCKETBOOK BERBASIS AUGMENTED REALITY MENGENAI PENCEGAHAN DIABETES MELITUS TIPE 2 PADA REMAJA - Diva Amimah Saputro; Atin Karjatin (Jurnal Kesehatan Siliwangi, 2025)
Background: The prevalence of diabetes mellitus in adolescents aged 15-24 years reached 159,014 cases in 2018. Bandung Regency ranked second with 59,205 patients, in the Banjaran City Health Center area experienced an increasing trend, in 2022 there were 356 patients with diabetes mellitus aged 15 years and over who received health services according to standards. This number to 1,761 patients in 2023, with an increase of 394.66%. Therefore, preventive efforts are needed to reduce the rate of increase in diabetes mellitus cases through education using media tools that can help increase knowledge. Objective: Developing Augmented Reality-based E-PocketBook Educational Media regarding the prevention of Type 2 diabetes mellitus in adolescents with a 4D approach. Method: Research method used is R&D (Research and Development) with a 4D approach, namely Define, Design, Development which consists of material tests, media tests, small-scale tests, then quantitative tests using Quasi Experimental Design and one-group pretest-posttest design design to 51 adolescents and Dissemination. Results: Results of the needs analysis stage (define) the target needs digital media that contains brief information, has pictures, is interesting, interactive and easy to understand. The media design determined is an augmented reality-based e-pocketbook, Development (development) obtained media is very feasible to use and there is an influence on adolescent knowledge about preventing type 2 diabetes mellitus. Dissemination through links and QR codes that are directly integrated with the heyzine e-pocketbook platform. Conclusion: Augmented reality-based e-pocketbook educational media can be used for the prevention of Type 2 Diabetes Mellitus in adolescents.